Cancer review: Cholangiocarcinoma - Yezaz Ahmed Ghouri (Journal of Carcinogenesis, 2015)
Cholangiocarcinoma (CCA) is the most common biliary tract malignancy. CCA is classified as intrahepatic, perihilar or distal extrahepatic; the individual subtypes differ in their biologic behavior, clinical presentation, and management. Throughout the last decades, CCA incidence rates had significantly increased. In addition to known established risk factors, novel possible risk factors (i.e. obesity, hepatitis C virus) have been identified that are of high importance in developed countries where CCA prevalence rates have been low. CCA tends to develop on the background of inflammation and cholestasis. In recent years, our understanding of the molecular mechanisms of cholangiocarcinogenesis has increased, thereby, providing the basis for molecularly targeted therapies. In its diagnostic evaluation, imaging techniques have improved, and the role of complementary techniques has been defined. There is a need for improved CCA biomarkers as currently used ones are suboptimal. Multiple staging systems have been developed, but none of these is optimal. The prognosis of CCA is considered dismal. However, treatment options have improved throughout the last two decades for carefully selected subgroups of CCA patients. Perihilar CCA can now be treated with orthotopic liver transplantation with neoadjuvant chemoradiation achieving 5-year survival rates of 68%. Classically considered chemotherapy-resistant, the ABC-02 trial has shown the therapeutic benefit of combination therapy with gemcitabine and cisplatin. The benefits of adjuvant treatments for resectable CCA, local ablative therapies and molecularly targeted therapies still need to be defined. In this article, we will provide the reader with an overview over CCA, and discuss the latest developments and controversies.